Comparison of effectiveness and safety of TAVI and SAVR in treatment of severe, symptomatic aortic stenosis – a literature review - Zydlewski, Igor; Blecharczyk, Małgorzata; Mrozek, Martyna; Pacanowska-Trawnicka, Martyna; Jakimowicz, Aleksandra; Zielińska, Agnieszka; Kamińska, Zuzanna; Malcher, Aleksandra (Quality in Sport, 2026)
Introduction Aortic stenosis is the most common acquired, valvular heart disease among adults in developed countries. It causes exercise tolerance deterioration, left ventricle hypertrophy and leads to heart failure or even death. Available treatment methods for severe, symptomatic aortic stenosis include Transcatheter Aortic Valve Implantation and Surgical Aortic Valve Replacement (SAVR). While it has been proven that TAVI is superior to SAVR in patients with high surgical risk, there is still little data considering patients with lower risk profile. Aim of study The aim of this study is to assess the differences between TAVI procedure and the Surgical Aortic Valve Replacement in terms of their efficacy and safety in patients with severe aortic stenosis and low to intermediate surgical risk. This article is based on the analysis of randomised controlled trials published between years 2021 and 2026. Conclusion TAVI is a safe and effective alternative to SAVR in patients with severe, symptomatic aortic stenosis and low to intermediate surgical risk. It is associated with a lower incidence of major bleeding, stroke and myocardial infarction while presenting comparable or lower mortality in short to medium term. It is, however, correlated with more frequent vascular complications and pacemaker implantations. There is a need for further research on a larger group of patients, with a longer follow-up time in order to assess optimal guidelines for TAVI and SAVR in patients with this risk profile.